(untitled) (Journal Of Educational and Psychological Researches, 2022)
The research aims to measure the psychological security of social working in the courts, to measure the motivation of achievement for social researchers working in the courts. In addition to, identify the Psychological security and its relation to the motivation of achievement for social researchers working in the courts. To achieve these aims, the researcher adopted two scales: Maslow scale for Psychological security, which was translated to Arabic by Dwany and Dirany 1983 consisted of (75) items. The second scale is Othman scale for achievement motivation 2014 consisted of (24) items. The two scales had been applied to a sample consisted of (100) social researchers working in the courts of Baghdad with its two branches Al-karkh and Al-Risafa for the academic year (2018-2019). The researcher found out a correlation between Psychological security and motivation for the achievement of social researchers working in the courts. The researcher concluded this study with a number of recommendations and suggestions.